2013
DOI: 10.1017/s1478951513000217
|View full text |Cite
|
Sign up to set email alerts
|

Do spiritual patients want spiritual interventions?: A qualitative exploration of underserved cancer patients' perspectives on religion and spirituality

Abstract: Spirituality plays a central role in the cancer experience of this underserved ethnically-diverse population. While spirituality seems to be a universal concern in advanced cancer patients, the meaning of spirituality differs across individuals, with some equating it with organized religion and others taking a more individualized approach. It is important that psychosocial interventions are developed to address this concern. Future research is needed to further explore the different ways that patients conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
9
0
2
Order By: Relevance
“…Four themes emerged: connection, seeking peace, meaning and purpose, and transcendence. The spiritual needs highlighted in this study are similar to findings from studies conducted in other parts of the world (Murray et al 2004;Höcker et al 2014;Stein et al 2015).…”
Section: Qualitative Researchsupporting
confidence: 83%
“…Four themes emerged: connection, seeking peace, meaning and purpose, and transcendence. The spiritual needs highlighted in this study are similar to findings from studies conducted in other parts of the world (Murray et al 2004;Höcker et al 2014;Stein et al 2015).…”
Section: Qualitative Researchsupporting
confidence: 83%
“…43 Further, what comprises helpful experience and expression of R/S may vary tremendously across individuals and cultures; participants should be invited to draw upon their own faith traditions in dealing with their cancer diagnosis or treatment. Such expressions of faith may take on different characteristics across individuals and underscore the importance of tailoring interventions for optimal patient-centered care.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…For example, a study by Stein et al they found that while patients from ethnically diverse backgrounds used a spiritual and religious framework to understand their cancer journey, their conceptualization of these strategies varied greatly. [21] In addition, the above research has suggested that coping can influence or predict one's psychological and health outcomes, highlighting the need to study coping in cancer. The current paper aims to review the suitability and benefits of using qualitative research designs to understand coping with cancer with the help of some key literature in this area.…”
Section: Introductionmentioning
confidence: 99%